Dielectric behavior of XLPE aged under multi-stressing conditions - Leguenza, E. L.; Robert, R.; Moura, W. A.; Giacometti, J. A. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2005)
In this work fresh cables were laboratory aged under multi-stressing conditions at room temperature. Foils were peeled from cables, with approximately 150 ?m thickness, from the outer, middle and inner positions of the XLPE cable insulating layer. For samples obtained from the outer cable layer position, an increasing near-permanent electrical conduction process with aging time was observed. At the middle and inner cable layer positions a flat-loss relaxation process was observed becoming a dominating process on the ageing. In addition, PEA results confirmed that degradation in the outer region of the XLPE cables arises from the simultaneous presence of dipoles and injected space charge that distorts the internal electric field on the ageing.
Keywords: Dielectric properties; Electric conductivity; Electric insulation; Stress relaxation; Thermal stress; Dielectric behavior; Insulating layers; Multi stressing conditions; Room temperature; Electric cables